Jamunaa won two awards in the Chinese Bridge 2013 - Yong, Ying Mei
Faculty of Computer Systems & Software Engineering (FSKKP), Universiti Malaysia Pahang (UMP) undergraduate Jamunaa d/o Patchappan, 23, won two awards in the Chinese Bridge 2013 held at Hunan, China that began on July 1 until July 12, 2013.